Literacy project in kindergarten: oral and written practices - Ariane Ranzani; Patrícia Pereira (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2018)
This paper show the reflection about oral and written practices developed in kindergarten from a literacy project that enabled children to expand their cultural experiences with discursive genres. The pedagogical work involved children from kindergarten between 4 and 6 years old. Historical-Cultural Psychology (LEONTIEV, 1978a, 1978b, 2014a, 2014b; VYGOTSKI, 1995) and the New Literacy Studies (KLEIMAN, 2000; TINOCO, 2008) were the theoretical basis of this study. It is concluded that the child's access to different oral and written practices favors them to feel literate, while allowing her to assume different social roles and to appropriate the socio-historically elaborated knowledge.